Design and Development of Product Service Systems (PSS) - Impact on Product Lifecycle Perspective. (2016) - Wuest, Thorsten; Wellsandt, Stefan
Abstract: Product Service Systems (PSS) focus on the delivery of value to the customer and their continuous satisfaction. This overarching goal has to be reflected during the design and development of PSS. With the changing business models of PSS, away from a one-time sale towards a constant delivery of customer satisfaction and value, the whole lifecycle of a PSS is becoming increasingly important. A similar development can also be observed for 'traditional' products and services. However, for PSS this holistic emphasis can be considered a key factor for success. The changing requirements and needs brought forth by PSS and their impact on the 'traditional' PLM models are discussed in this paper. An emphasis is on the three-phase model and its presentation, which is often used to illustrate the product lifecycle from a technical and IT perspective. Finally, some adaptations for the traditional illustration are presented as a first starting point for further discussion and in-depth research within the community.